2011
DOI: 10.1089/jmf.2010.0195
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, Free Radical–Scavenging, and Cytotoxic Activities of Acanthus hirsutus Boiss

Abstract: In vivo antinociceptive and in vitro radical scavenging and cytotoxic activities of Acanthus hirsutus Boiss. aqueous extract were investigated to give a new insight into plant usage in traditional medicine. The extract showed significant antinociceptive activity in acetic acid-induced writhing test in mice after oral application and did not change the hind-leg retraction period in the hot-plate test for any dose applied. In addition, the extract showed radical-scavenging activity against 2,2-diphenyl-1-picryl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The two samples produced higher cytotoxic effects in SK‐MEL‐2 (25.41% and 30.74%, respectively) versus V79 cells (10.02% and 15.78%, respectively) at 100 μg/mL. These observations suggest that CME and EAE exhibited a slightly moderate selective antiproliferative effect on tumour cells; targeting only tumour cells without affecting the viability of normal ones is an important feature in the screening of novel anticancer candidates …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The two samples produced higher cytotoxic effects in SK‐MEL‐2 (25.41% and 30.74%, respectively) versus V79 cells (10.02% and 15.78%, respectively) at 100 μg/mL. These observations suggest that CME and EAE exhibited a slightly moderate selective antiproliferative effect on tumour cells; targeting only tumour cells without affecting the viability of normal ones is an important feature in the screening of novel anticancer candidates …”
Section: Resultsmentioning
confidence: 87%
“…Therefore, the results from the cytotoxicity and genotoxicity assays on normal cells conclude that CME and EAE obtained from V. ovalifolium aerial parts might not contain cytotoxic and genotoxic compounds. Indeed, previous reports showed that verbascoside, the major constituent of V. ovalifolium extracts, possessed reduced cytotoxicity in normal cells and no mutagenicity and genotoxicity in Salmonella thyphimurium strains, Drosphophila melanogaster and human peripheral lymphocytes …”
Section: Resultsmentioning
confidence: 99%
“…Harput et al [70] APO Murine macrophages were stimulated with LPS (2 g/mL) and IFN-␥ (10 IU/mL) in the presence or absence of various concentration of APO.…”
Section: Mboamentioning
confidence: 99%
“…From the search, 29 hits were found with different mangrove species reporting one or more of these activities: antinociceptive, anti-inlfammatory, and antipyretic activity (Tables 2 and 3) [432]. Some of the reports coincide for a given species, and, therefore, a total of 17 plants were reported to have such activity.…”
Section: Antinociceptive Anti-inflammatory and Antipyretic Activitymentioning
confidence: 99%
“…However, exploring the methods applied in the published reports on evaluation of antinociceptive, anti-inflammatory, and/or antipyretic activity of mangrove plants [4–34], the following assumptions can be made about the possible mechanisms of actions. The sensation of pain can be initiated either peripherally or through the central nervous system.…”
Section: Possible Mechanism Of Actionsmentioning
confidence: 99%